Engineering immunity with CAR-NK cells: advancing the frontiers of cancer immunotherapy - Cianga, Vlad Andrei; Antohe, Ion; Minciună, Cosmin; Dăscălescu, Angela (Frontiers in Pharmacology, 2025)
Chimeric antigen receptor–modified natural killer (CAR-NK) cells are emerging as a promising alternative to CAR-T therapies, offering advantages such as reduced toxicity, allogeneic feasibility, and flexible manufacturing. Current reviews cover NK biology and CAR engineering progress, yet lack a unified perspective that connects these advances. This review provides a novel synthesis by mapping specific tumor immune evasion mechanisms, including antigen loss, lineage plasticity, impaired antigen processing, epitope masking, and trogocytosis to corresponding next-generation CAR-NK engineering solutions. This “evasion-to-solution” framework highlights how innovations such as dual-antigen CARs, low-affinity designs, NK-specific signaling, iPSC-derived NK platforms, and multiplex gene editing directly mitigate known mechanisms that lead to therapeutic failure. By linking tumor biology to engineering strategy, this review offers a translational roadmap for the rational design of more adaptable and resilient CAR-NK therapies.